Global slowing of network oscillations in mouse neocortex by diazepam - Scheffzük, Claudia; Draguhn, Andreas; Brankačk, Jurij (Neuropharmacology, 2013)
Benzodiazepines have a broad spectrum of clinical applications including sedation, anti-anxiety, and anticonvulsive therapy. At the cellular level, benzodiazepines are allosteric modulators of GABA(A) receptors; they increase the efficacy of inhibition in neuronal networks by prolonging the duration of inhibitory postsynaptic potentials. This mechanism of action predicts that benzodiazepines reduce the frequency of inhibition-driven network oscillations, consistent with observations from human and animal EEG. However, most of existing data are restricted to frequency bands below ∼30 Hz. Recent data suggest that faster cortical network rhythms are critically involved in several behavioral and cognitive tasks. We therefore analyzed diazepam effects on a large range of cortical network oscillations in freely moving mice, including theta (4-12 Hz), gamma (40-100 Hz) and fast gamma (120-160 Hz) oscillations. We also investigated diazepam effects over the coupling between theta phase and the amplitude fast oscillations. We report that diazepam causes a global slowing of oscillatory activity in all frequency domains. Oscillation power was changed differently for each frequency domain, with characteristic differences between active wakefulness, slow-wave sleep and REM sleep. Cross-frequency coupling strength, in contrast, was mostly unaffected by diazepam. Such state- and frequency-dependent actions of benzodiazepines on cortical network oscillations may be relevant for their specific cognitive effects. They also underline the strong interaction between local network oscillations and global brain states.